Modern weapons and military equipment for issue 2-2018 - Jevtić, Miloš M (Vojnotehnički glasnik / Military Technical Courier, 2018)
Usage of Semi-auto and bolt action sniper rifles in police actions. About sniping specialists, modus of their activation and their armament.